An in vivo transfection system for inducible gene expression and gene silencing in murine hepatocytes. (January 2017) - Hubner, Eric K.; Lechler, Christian; Kohnke‐Ertel, Birgit; Zmoos, Anne‐Flore; Sage, Julien; Schmid, Roland M.; Ehmer, Ursula
Abstract: Background: Hydrodynamic tail vein injection (HTVI) of transposon‐based integration vectors is an established system for stably transfecting mouse hepatocytes in vivo that has been successfully employed to study key questions in liver biology and cancer. Refining the vectors for transposon‐mediated hepatocyte transfection will further expand the range of applications of this technique in liver research. In the present study, we report an advanced transposon‐based system for manipulating gene expression in hepatocytes in vivo . Methods: Transposon‐based vector constructs were generated to enable the constitutive expression of inducible Cre recombinase (CreER) together with tetracycline‐inducible transgene or miR‐small hairpin RNA (shRNA) expression (Tet‐ON system). Transposon and transposase expression vectors were co‐injected into R26R‐mTmG reporter mice by HTVI. Cre‐mediated gene recombination was induced by tamoxifen, followed by the administration of doxycycline to drive tetracycline‐inducible gene or shRNA expression. Expression was visualized by immunofluorescence staining in livers of injected mice. Results: After HTVI, Cre recombination by tamoxifen led to the expression of membrane‐bound green fluorescent protein in transfected hepatocytes. Activation of inducible gene or shRNA expression was detected by immunostaining in up to one‐third of transfected hepatocytes, with an efficiency dependent on the promoter driving the Tet‐ON system. Conclusions: Our vector system combines Cre‐lox mediated gene mutation with inducible gene expression or gene knockdown, respectively. It provides the opportunity for rapid and specific modification of hepatocyte gene expression and can be a useful tool for genetic screening approaches and analysis of target genes specifically in genetically engineered mouse models.